Beware of Pleural Thickening and Calcification: An Enlightenment from a Case of Tuberculous Pleurisy - Zhu Y; Gao YH; Zou JN; Xi EP (Dove Medical Press, 2021)
Yu Zhu,1,* Yan-Hong Gao,2,* Jia-Ni Zou,3 Er-Ping Xi1 1Department of Thoracic Cardiovascular Surgery, General Hospital of the Central Theater Command of the People’s Liberation Army, Wuhan, 430070, People’s Republic of China; 2Department of Ultrasound, General Hospital of the Central Theater Command of the People’s Liberation Army, Wuhan, 430070, People’s Republic of China; 3Department of Radiology, General Hospital of the Central Theater Command of the People’s Liberation Army, Wuhan, 430070, People’s Republic of China*These authors contributed equally to this workCorrespondence: Er-Ping Xi; Jia-Ni ZouGeneral Hospital of the Central Theater Command of the People’s Liberation Army, 627#, Wuluo Road, Wuchang District, Wuhan, Hubei, 430070, People’s Republic of ChinaTel +86-13871160246Fax +86-27-50772388Email wo5351@126.com; dor_nizming@163.comAbstract: Tuberculous pleurisy, a type of extra-pulmonary tuberculosis, is the pleural inflammation caused by hypersensitive response of the pleural cavity stimulated by mycobacterium tuberculosis and its metabolites. If the patient does not receive timely and effective treatment and intervention, a large amount of fibrin will be deposited which will cause pleural thickening, adhesions, and even calcification. At present, clinical cases of typical pleural thickening and calcification have been rarely reported. In this paper, we will report a case of significant pleural thickening and calcification caused by tuberculous pleurisy; moreover, the patient earliest got tuberculous pleurisy about in 20 years ago and had received anti-tuberculous treatment at that time. The patient’s typical crescent-shaped shadow created by pleural thickening and calcification is very rare in the domestic and international literature.Keywords: tuberculosis, pleura, thickening, calcification